Examining diabetic heel ulcers through an ecological lens: microbial community dynamics associated with healing and infection. Issue 2 (9th January 2019) - Sloan, Tim J.; Turton, James C.; Tyson, Jess; Musgrove, Alison; Fleming, Vicki M.; Lister, Michelle M.; Loose, Matthew W.; Sockett, R. Elizabeth; Diggle, Mathew; Game, Frances L.; Jeffcoate, William
Abstract : Purpose. While some micro-organisms, such as Staphylococcus aureus, are clearly implicated in causing tissue damage in diabetic foot ulcers (DFUs), our knowledge of the contribution of the entire microbiome to clinical outcomes is limited. We profiled the microbiome of a longitudinal sample series of 28 people with diabetes and DFUs of the heel in an attempt to better characterize the relationship between healing, infection and the microbiome. Methodology. In total, 237 samples were analysed from 28 DFUs, collected at fortnightly intervals for 6 months or until healing. Microbiome profiles were generated by 16S rRNA gene sequence analysis, supplemented by targeted nanopore sequencing. Result/Key findings. DFUs which failed to heal during the study period (20/28, 71.4 %) were more likely to be persistently colonized with a heterogeneous community of micro-organisms including anaerobes and Enterobacteriaceae (log-likelihood ratio 9.56, P =0.008). During clinically apparent infection, a reduction in the diversity of micro-organisms in a DFU was often observed due to expansion of one or two taxa, with recovery in diversity at resolution. Modelling of the predicted species interactions in a single DFU with high diversity indicated that networks of metabolic interactions may exist that contribute to the formation of stable communities. Conclusion. Longitudinal profiling is an essential tool for improving our understanding of the microbiology of chronic wounds, as community dynamics associated with clinical events can only be identified by examining changes over multiple time points. The development of complex communities, particularly involving Enterobacteriaceae and strict anaerobes, may be contributing to poor outcomes in DFUs and requires further investigation.